PRODUCTION ANALYSIS AND REVENUES OF GOURAMY HATCHERY BUSINESS IN NAGARI MUNGO LUAK SUBDISTRICT FIFTY CITYDISTRICT WEST SUMATERA PROVINCE - Mezi Agus Safputri; Hendrik Hendrik; Darwis A.N2 (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This research was conducted in March 2017 in Nagari Mungo Luak Subdistrict fifty City District West Sumatra Province. The purpose of this study was to analyze the efficiency of the use of production factors in the gouramy hatchery business, analyzing the income of gouramy fish farmers, to analyze BEP value of acceptance, BEP production and BEP price. The method used in this research is survey method with total population of gouramy fish cultivators 120 people taken as many as 36 people. The respondent collected using random sampling technique.The technical analysis used areNPM/BKM ratio analysis, income analysis, BEP analysis. Based on the results of research indicate that: The use of production factors of hatchery gouramy has not efisisen. Gross income of gurami hatchery business in Nagari Mungo is Rp 37,569,444/ 3 months and net income is Rp 30,680,137. For the BEP value of the average revenue of fish breeding gouramy Rp 944.496, BEP average production of 609 heads, and BEP average price of 100 Rp / head. Keywords: Production, Efficiency, Income, Gouramy Fish